Case Report: Surgical Management of Painful Manubriosternal Pseudoarthrosis - Bar-Haim, Ronit; Shtarker, Haim; Biswas, Seema; Waksman, Igor; Altman, Edward (Frontiers in Surgery, 2021)
A 31-year-old male amateur bodybuilder presented with a two-year history of chronic pain over the sternum and a clicking sensation in the chest wall on movement. Ultrasound, computer tomography (CT), and magnetic resonance imaging, (MRI), showed no cause for his symptoms. Dynamic ultrasound scan performed at a specialist sports center revealed pseudoarthrosis of the manubriosternal joint (MSJ). After a period of conservative management (rest and analgesia) he failed to improve and underwent debridement and fusion of the MSJ with plates and screws. At follow up 23 months later he remains pain free and has returned to weightlifting and body building.